HIGH INTERLEUKIN-6, LOW CD4+ AND CD8+ T-LYMPHOCYTES EXPRESSIONS AS RISK FACTORS OF CERVICAL CARSINOMA INFECTED BY HUMAN PAPILLOMA VIRUS TYPE-52 - Mahendra-Dewi, I G. A. S,; Suwiyoga, I K.; Joewarini, E.; Alit-Artha,; I G. (Udayana University, 2013)
In Indonesia cervical carcinoma is the most common cancer in women and one of the leading cause of mortality. High risk human papillomavirus (HPV) is the major risk factor of cervical cancer. This study aims to know the role of IL-6, CD4+ and CD8+ T-lymphocyte for the risk of cervical carcinoma infected by HPV52. This study was a case control study, specimens of cervical carcinoma patients infected by HPV type-52 as the case group and HPV type-16 or 18 as the control group. HPV genotyping used SPF10 primer and type specific E7 primer by LiPA. Immunohistochemistry method was used to know expression of IL-6, CD4+ and CD8+ T lymphocyte. Pearson’s c2 test was applied with statistical significance was set at the 2-sided 0.05 level. The odds ratios (OR) were calculated for the risk, with 95% confidence intervals on SPSS 16.0 for windows. PCR examination was performed in 185 paraffin-embedded tissue. The risk of high IL-6 expression in cervical carcinoma infected by HPV type-52 was statistically significant 6-fold higher compare with cervical carcinoma infected by HPV type 16 (OR = 6.00 ; CI 95% = 1.13-31.99; p = 0.03; p < 0.05) and HPV type 18 (OR = 6.00 ; CI 95% = 1.13-31.99; p = 0.03; p < 0.05). The risk of low CD4+ T lymphocyte expression in cervical carcinoma infected by HPV type 52 was statistically significant 6-fold higher and 7.43-fold higher respectively compare with cervical carcinoma infected by HPV type 16 (OR = 6.00 ; CI 95% = 1.003-35.91; p = 0.04; p < 0.05) and HPV type 18 (OR = 7.43 ; CI 95% = 1.23-45.01; p = 0.02; p < 0.05). The risk of low CD8+ T lymphocyte expression in cervical carcinoma infected by HPV type 52 was statistically significant 13.5-fold higher and 11-fold higher respectively compare with cervical carcinoma infected by HPV type 16 (OR = 13.50 ; CI 95% = 1.42-128.26; p = 0.01; p < 0.05) and HPV type 18 (OR = 11.00 ; CI 95% = 1.16-103.94; p = 0.02; p < 0.05). No significance different between cases and controls group in mean-age, parity and sexual activity (p > 0.05). In conclusion, this study found that high IL-6 expression, low CD4+ and CD8+ T lymphocyte expression were the risk factors of cervical carcinoma infected by HPV type 52.